Protocol for a randomized controlled trial of a combined motivational interviewing and behavioral couples therapy intervention to reduce intimate partner violence and alcohol use in south India - Meghna Achar; Megan Ramaiya; Krishnamachari Srinivasan; Maria L. Ekstrand; Elsa Heylen; Johnson Pradeep R; Miriam Hartmann; Nisha C. K; Matilda Pereira; Bibhav Acharya (PLoS ONE, 2025)
There is a strong association between alcohol use disorder (AUD) and intimate partner violence (IPV), both widely prevalent global health issues. However, few interventions target both IPV and AUD, include both partners in the intervention, and are delivered by non-specialist providers in low- and middle-income country (LMIC) settings with scarce mental health resources. This paper describes the protocol for a randomized controlled trial of a combined motivational interviewing (MI) and behavioral couples therapy (BCT) intervention delivered in urban primary care settings in India by nurses with no behavioral health training prior to joining the study. A total of 400 couples will be enrolled and randomized to one of two arms: an intervention arm comprised of 10, hour-long sessions of the MI + BCT intervention, and a control arm receiving enhanced usual care and medical-legal referrals. Data collection will take place at five timepoints: baseline (pre-intervention), three-, six-, nine-, and 12-month follow-ups. Primary quantitative outcomes include the frequency of intimate partner violence over the last 6 months and self-reported quantity and frequency of alcohol use, drinking behaviors, and alcohol-related problems as assessed on the Alcohol Use Disorders Identification Test (AUDIT). Secondary outcomes include number of days with a negative breathalyzer test over a one-week period, communication patterns, and the quality of marital relationship. Qualitative interviews with a sub-sample (n = 40 couples) from the intervention arm will take place immediately post-intervention and at 12 months to explore underlying mechanisms of change. If successful, study results can inform future efforts to develop scalable interventions for IPV and AUD that can be sustained in the Indian public health system through existing PHC staff and infrastructure and be adapted to similar sociocultural settings.